Utilizing the physical green care environment to support activities of daily living for nursing home residents: a focused ethnographic case study - Svenja Cremer; Katharina Rosteius; Sandra M.G. Zwakhalen; H. Verbeek; Michel H.C. Bleijlevens; Bram de Boer (BMC, 2024)
Abstract Background The nursing home residents' ability to carry out Activities of Daily Living (ADLs) is influenced by the physical care environment. One emerging area of interest in scientific research is the green care environment within nursing home care, where agricultural activities such as gardening and animal care are integrated alongside daily care. Previous research has neglected to explore how these environments can be employed to enhance ADL performance. This study, therefore, explores how a green care environment, specifically one with an animal shelter, can be used to support nursing home residents in their ADLs. Methods A focused ethnographic case study was conducted in one nursing home. Data was collected employing participatory observations, informal conversations, and semi-structured interviews, which we analyzed by employing a thematic analysis. Results Overall, 25 residents were observed for a total time of 89h, and interviews were conducted with 10 staff members. The nursing home integrates activities in the green care environment into daily care for a broad scope of residents. The analysis revealed four themes: (1) The (in)visibility of ADL, (2) Reciprocal care dynamics: Fostering ADL performance through connection and teamwork, (3) Seized and missed opportunities for meaningful integration of ADL in the physical green care environment, and Theme (4) Professional fulfillment and ADL task obligation: Views from staff and management. Conclusions This physical green care environment carries the potential to enhance the residents' daily activities and foster better staff-resident relationships. Yet, there are varying views among staff and management regarding its integration into the residents' lives and care.